Women and Malaysian Islamic Family Law: towards a women-affirming jurisprudential reform - Haneef, Sayed Sikandar Shah (Routledge, 2011)
Codification of Islamic family law indeed has been one of the most effective ways of administering Islamic law in the modern time. It is obviously due to its many advantages including making the law certain, uniform and supposedly in tandem with the current needs of society in a modern setting, particularly in solving issues facing Muslim women in contemporary families. Nevertheless according to critics, this legislative measure has not been free of pitfalls and loopholes, which have pathetically worked against womens` welfare in many ways. In the Malaysian context, for examples, the most prominent allegation is the gender-bias feature of certain provisions of the applicable law. To remedy the situation, given the cultural sensitivity and moorings of different interest groups in the country, the approaches have been diverse. But by looking at the issue from a purely academic- nonpartisan perspective, one would assume that the problem is rooted in the way that the legislature has construed fiqh and codified it in the form of the existing statutes. In this paper, therefore, we attempt to analytically explore as to what to undo in the existing laws in order to make them more robust, effective and responsive to the need of Muslim women in the 21st century.